Peter Rabbit 2 [videorecording (DVD)] - Byrne, Rose; Gleeson, Domhnall, 1983-; Oyelowo, David; Potter, Beatrix, 1866-1943 (Sony Pictures Home Entertainment, 2021)
Bea, Thomas, and the rabbits have created a makeshift family, but despite his best efforts, Peter can't seem to shake his mischievous reputation. Adventuring out of the garden, Peter finds himself on the mean streets of the city where his mischief is appreciated, but when his family risks everything to come looking for him, Peter must figure out what kind of bunny he wants to be.